Podważenie stereotypów dyskursu wołyńskiego w polskim reportażu literackim i filmowym - Risìč-Šafranêc, Ûlìâ (Instytut Kultury Regionalnej i Badań Literackich im. Franciszka Karpińskiego Stowarzyszenie. Wydawnictwo Naukowe, 2019)
Volhynian discourse in Polish-Ukrainian dialogue in various spheres of communication are considered in the article. On the one hand, a communicative characteristic of speech acts filling this discourse is given; on the other hand, the stereotypes that appear throughout all stages of its development are shown. The phenomenon of the de-stereotyping of the most persistent cliches of the Volhynian discourse in Polish art and documentary reportage was noted and presentation of it was the goal of the study. The analysis showed that firstly, there is the tendency to de-stereotyping and the predominance of cognitive function in the artistic channel of the discourse development; secondly, the dominance of the Volhynian discourse in the current Polish-Ukrainian dialogue at the political level and in the social-media channel, and as a result - the fading of the dialogue and
Keywords: discourse; communication sphere; foundations of speech acts; stereotype; дискурс; сфера коммуникации; функции речевых актов